DEVELOPING YOUTUBE VIDEO-BASED LEARNING MATERIAL FOR TOURISM STUDY PROGRAM AT GUNADARMA UNIVERSITY - Salsabila; Widyo Nugroho; Ichwan Suyudi (Journal of Research and Innovation In Open and Distance Learning, 2023)
YouTube as one of the most popular inventions on the internet, could be used as a teaching and learning medium, such as studying English for specific purposes, in this example for the tourism study program. The study aimed to create video-based English teaching material for Gunadarma University's tourism students, as well as to collect feedbacks from students. The study employed a mixed-method approach and the R&D method developed by Borg and Gall in this study for creating a teaching and learning video. This study developed English teaching materials in video format that were uploaded on YouTube. The video learning material was reviewed by media and content experts, as well as 30 tourism students in academic year 2020/2021. The result has shown for display quality by experts was 86,00 % satisfactorily, media quality was 81,33% and for lesson quality was 85,45% respectively. Meanwhile the result from students showed for display quality was 86,25% and for material presentation was 92,88%. Among display quality and content presentation in students’ survey, the highest percentage score was content presentation which received 92,88% satisfactorily. In conclusion, the video learning material was considered interesting and helpful for learning English for tourism students.